Alternative profit rate shariah-compliant for islamic banking - Nadhirah, Gazali; Nurfadhlina, Abdul Halim; Puspa Liza, Ghazali (2017)
Profit is the aims for Islamic banking and conventional banking. Determination of profit in Islamic banking in Malaysia depends on the profit rate, whereas profit rate is essentially from reference rate which is known as the base rate (BR). However, the determination of the components contained in the BR such as benchmark cost of funds and the statutory reserve requirement (SRR) is non-compliance with the Shariah because its directly proportional to the overnight policy rate (OPR). Therefore, an alternative formula for the profit rate are proposed which is known as the base profit rate (BPR). Construction of BPR formula is based on the principle that are more Shariah-compliant.